(3GdHdZI def dGjMVQg GdeaSQs - (3GdYHGS eMeO Hf eMeO Hf CMeO GdMce GdWhSjs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdbOje GdYOd GdMcje s
(3BNQgG (B:s
(3jfJgi HBNQ JaSjQ ShQI Gdcga , hBNQ eG ajg (B:" (3Yf QShd Gddg Udi Gddg Ydjg hSde (B: (3ef bQC ShQI Gdcga agh eYUhe KeGfjI CjGe ef cd aJfI hGdMeO ddg hMOg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs